1996
DOI: 10.1007/bf02784182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium in soluble glass bolus on selenium content of milk and blood of goats

Abstract: Soluble glass bolus (SGB) with selenium (Se) was administered intraruminally to Se-deficient Philippine does to determine its effect on milk Se and to correlate the Se contents of does' milk and blood of does and kids. Five months after the Se administration, the does in the treated group (n = 14) had higher (p < 0.01) Se content in their blood (62.2 vs 25.7 micrograms/L) and milk (5.1 vs 2.5 micrograms/L) than does in control group (n = 13). Consequently, the blood Se of the kids (n = 14) from the treated doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 14 publications
1
15
0
2
Order By: Relevance
“…2). However, Serra et al . (1996), also working in the same area, reported Se values of 62.2 and 25.7 ng/mL for the SGB and control groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). However, Serra et al . (1996), also working in the same area, reported Se values of 62.2 and 25.7 ng/mL for the SGB and control groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…(2003) reported positive effects of improving the blood Se status of grazing goats through an intra‐ruminal administration of Se soluble glass bolus (SGB). In an on‐farm study, also in the Philippines, Serra et al . (1996) reported that kids born from does administered with SGB had a high blood Se concentration.…”
Section: Introductionmentioning
confidence: 99%
“…It is very likely that if there was a lack of selenium in the basic feed, the selenium supplementation would be reflected in the increased concentration of selenium in milk. Serra et al (1996) were interested in the effect of selenium in soluble grass bolus on the selenium content of milk and blood of goats. These authors found that five months after Se administration, the does in the treated group had a higher (p < 0.01) Se content in their blood (62.2 vs. 25.7 μg·l -1 ) and milk (5.1 vs. 2.5 μg·l -1 ) than does in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…15 Oral supplementation of mature does increased the average blood Se concentrations to 6.22 mg/dl in the does and 2.80 mg/dl in their kids. These values are lower than the suggested threshold concentration of 7 mg/dl and are below that at which livestock species are considered to be Se deficient.…”
mentioning
confidence: 99%
“…15 However, a study in New Zealand determined that nutritional muscular dystrophy caused by Se deficiency was the leading cause of mortality in goat kids between the ages of 1 and 9 weeks. 2 Nutritional muscular dystrophy was rarely diagnosed in cattle or sheep in the same area of the country, but differences in supplementation were not specifically addressed.…”
mentioning
confidence: 99%